Influence of an orthodeuterium impurity on the thermal conductivity of solid parahydrogen - Korolyuk, O. A.; Gorodilov, B. Ya.; Krivchikov, A. I.; Manzhelii, V. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The thermal conductivity of solid parahydrogen with orthodeuterium impurity at the impurity concentration from 0.01 to 1% has been studied in the temperature range from 1.8 to 9 K. The nonlinear concentration dependence of the thermal resistivity of the investigated samples is explained by the fact that the intensity of normal three-phonon scattering processes is comparable to that of resistive processes. The analysis of the experimental results has been made in the framework of the Callaway model by using different models for the impurity phonon scattering. It has been found that the intensity of phonon impurity scattering in parahydrogen with orthodeuterium impurity is essentially higher than classical theory predicts and it is close to analogous scattering in solutions of helium isotopes with the equal reduced molar volume given. It is considered that additional impurity scattering of phonons is connected with the change of force constants and lattice distortion in the vicinity of impurity molecules. The quantitative estimation of the mentioned effects has been made.